Stratégies de partage et diffusion de données publiques environnementales - Sandra Nicolle; Maya Leroy (Netcom)
In this article, we analyse and compare the strategies implemented by France and Brazil regarding the production and distribution of monitoring data concerning the impact of human activities in an Amazonian context : gold mining impacts in French Guiana, and agricultural development impacts in Brazil. We show that independently of the legislation, the strategies implemented by each of the two countries are very different, with consequences on the positioning and demands of civil society toward these data. Over the course of the last decade, the Brazilian government showed a tendency towards the opening access to deforestation monitoring data, under the pressure for transparency coming from national NGOs and from the international level. On the contrary, in French Guiana, there is a reduction of information distribution concerning gold mining impacts, linked to an increased involvement of national security state services in the monitoring process.